A SysML profile for smart city applications - Souza, Layse Santos (2021)
A smart city is an urban center that integrates a variety of solutions to enhance infrastructure performance and achieve sustainable urban development. Urban roads are a critical infrastructure highly demanded by citizens and organizations interested in their deployment, performance, and safety. Urban traffic signal control is a major and challenging problem in the real world, which aims to monitor and enhance traffic congestion. Therefore, the deployment of traffic signals for vehicles or pedestrians at a junction is a complex activity, as it is necessary to establish rules to control the flow of vehicles and pedestrians. Also, traffic flow at intersections changes constantly, depending on weather conditions, day of the week, and period of the year, as well as road works and accidents that further influence complexity and performance. This thesis first describes SmartCitySysML, a proposed profile that adapts SysML with special elements that are specific to smart cities. In addition, an extension of the SmartCitySysML profile to the design of the dimensions of smart cities is proposed. Finally, integration of models is performed, that is, the integration of the SmartCitySysML profile with Petri Net to separately model the basic architectural elements (sensor, controller, and actuator) of an urban traffic control system as sub-models to describe the behavior of each element, and the integration of the SmartCitySysML profile with Timed Coloured Petri Nets (TCPN) for modeling, simulation, and verification of properties of an urban traffic signal control system. CPN tools allow the evaluation of the model behavior through simulation and property verification and perform a simulation-based performance. Model simulation allows observing the behavior of the system under conditions that would be difficult to organize in a truly controlled environment. Consequently, a preliminary evaluation can be performed in the early stages of system development, significantly reducing costs of improvements and increasing quality of the final product.